As relações compositor/performer como eixo de processos criativos e abordagens analíticas - Pizaia, Daniel Gouvea (2022)
This research proposes to identify how the composer-performer relationships occur in creative processes associated with the indeterminacy, collaboration and the Paulo de Assis proposition of the emancipated performer. These approaches share an argument for claiming the status of the performer as a creative subject in the elaboration of the work. Although we can see in these arguments a critique of the performance norms associated with artistic processes, the statements do not renounce central categories of understanding and classification of the practice: the difference between performer and composer roles and the work as a regulative concept. We begin by a historical examination of the advent of the musical work and its impact on the norm of a praxis. We then proceed to investigate analytical approaches that propose a critique of this norm, changing the musical object from text to performance analysis. Finally, we propose a bibliographic review of case reports related to the three chosen approaches in order to map the composer-performer relationship through actions and behaviors identified in empirical experiences. This mapping will be based on the concept of Invariancy, associated with Fiel da Costa’s morphological approach, adapted to the scope of musical behaviors. The results of the analysis suggest that the artistic practices related to indeterminacy, collaboration and the proposal of the emancipated performer are not fundamentally characterized by a problematization of the dualistic relationship of identities, but for the maintenance of functions and roles. The difference about norm and normal proposed by Foucault, respectively associated with Discipline and Biopower, becomes a relevant conceptual mechanism for understanding the power relations between the subjects involved. The composer/performer relationships updated in the experiences can be understood as instances of biopower, since they replace the prescriptive and individualizing character of the norm for a continuity of a distinction of roles updated in more flexible levels of behavior and guaranteed by a statistical mechanism.